2020
DOI: 10.33603/jnpm.v4i1.3316
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Kesalahan Jawaban Mahasiswa Pada Mata Kuliah Trigonometri Berdasarkan Dimensi Pengetahuan Krathwohl

Abstract: Abstrak. Penelitian ini bertujuan untuk menganalisis dan mendskripsikan factorfaktor penyebab terjadinya kesalahan dalam menyelesaikan soal-soal trigonometri berdasarkan dimensi pengetahuan Krathwohl. Metode penelitian ini adalah kualitatif dengan jenis penelitian deskriptif. Subjek penelitian yaitu 29 orang mahasiswa program studi pendidikan matematika IKIP Siliwangi. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah tes tulis dan wawancara. Analisis data dilakukan dengan tiga langkah yaitu r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
5
0
5
Order By: Relevance
“…The results showed that the errors of the first semester students in solving the problem of applying the radian measurement consisted of misconception and factual errors. The results of this research are in accordance with the results of previous researches which showed that students experienced misconceptions and also errors in facts in solving trigonometry problems (Gür, 2009;Hidayat & Aripin, 2020;Imelda, 2018;Jaelani, 2017;Nabie et al, 2018;Setiawan, 2021cSetiawan, , 2021aSetiawan, , 2021bSetiawan, , 2021d.…”
Section: Types Of Errors Error Descriptionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that the errors of the first semester students in solving the problem of applying the radian measurement consisted of misconception and factual errors. The results of this research are in accordance with the results of previous researches which showed that students experienced misconceptions and also errors in facts in solving trigonometry problems (Gür, 2009;Hidayat & Aripin, 2020;Imelda, 2018;Jaelani, 2017;Nabie et al, 2018;Setiawan, 2021cSetiawan, , 2021aSetiawan, , 2021bSetiawan, , 2021d.…”
Section: Types Of Errors Error Descriptionsupporting
confidence: 91%
“…The research on prospective teachers' errors in solving trigonometric problems has been carried out previously by several researchers, namely (Gür, 2009;Hidayat & Aripin, 2020;Imelda, 2018;Jaelani, 2017;Nabie et al, 2018;Setiawan, 2021cSetiawan, , 2021aSetiawan, , 2021bSetiawan, , 2021d. The research results of Gür (2009) show that students still experience errors in the form of using inappropriate equations.…”
Section: Introductionmentioning
confidence: 99%
“…Some students were wrong in finding the variable of asked questions in the algebra concept. It occurred because students have a lack of ability in doing algebra, while algebra takes an important role to be connected in trigonometry (Demir & Heck, 2013;Hidayat & Aripin, 2020). For the calculation error, students were wrong in determining the value of trigonometry ratio and calculating the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it covers the study of triangles, the relationships between their sides and angles, the functions of sine and cosine, tangent and cotangent, secant and cosecant (Walsh et al, 2017). Trigonometry is a critical topic in mathematics in order to prepare students for advanced mathematics, including calculus (Hidayat & Aripin, 2020;Hidayat & Riyana, 2021). Aside from its importance for advanced mathematics, trigonometry contributes to many applications in non-mathematical fields such as architecture, civil engineering, cartography, geophysics and other advanced fields (Galarza, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with research which reveals that during teaching trigonometric material, the difficulties that are carried out by students mostly lie in the basic concepts of the material. Students know the concepts given by the teacher but have difficulty applying these concepts to problem solving [20]. answered incorrectly, a student just remembered and visualized the graph of y = sin x when the form equation is changed then the student is not able to communicate and draw the graphic.…”
Section: Resultsmentioning
confidence: 99%